2008
DOI: 10.1108/17563780810893482
|View full text |Cite
|
Sign up to set email alerts
|

Constrained optimization with an improved particle swarm optimization algorithm

Abstract: Purpose -The purpose of this paper is to present a new constrained optimization algorithm based on a particle swarm optimization (PSO) algorithm approach. Design/methodology/approach -This paper introduces a hybrid approach based on a modified ring neighborhood with two new perturbation operators designed to keep diversity. A constraint handling technique based on feasibility and sum of constraints violation is adopted. Also, a special technique to handle equality constraints is proposed. Findings -The paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In formula (6),there are six base random variables,σ 1 , σ 2 , σ 3 ,m , s, σ c. The statistical parameters [10] Processing of the constraint condition: taking the limit state equation's form and the random variables' mean and variance into consideration, we choose m which expressed with other variable as the dependent variable.…”
Section: Discussion Of the Real Genetic Algorithm's Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In formula (6),there are six base random variables,σ 1 , σ 2 , σ 3 ,m , s, σ c. The statistical parameters [10] Processing of the constraint condition: taking the limit state equation's form and the random variables' mean and variance into consideration, we choose m which expressed with other variable as the dependent variable.…”
Section: Discussion Of the Real Genetic Algorithm's Performancementioning
confidence: 99%
“…Newly proposed evolutionary techniques are also widely used in solving COPs, e.g. evolutionary differential [4], [5]; particle swarm optimization [4]; artificial immune system [6]; and so on. The latest review on constraint-handling techniques with evolutionary algorithms could be found in the literature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since its original version in 1995, the PSO algorithm has been expanded to solve a variety of different problems [100]. Multimodal, constrained, and multiobjective optimization problems are some of the most prominent applications that have been addressed with the PSO algorithm [132].…”
Section: Particle Swarm Optimization Convergencementioning
confidence: 99%
“…Particle Swarm Optimization(PSO), an emerging population-based heuristic optimization method originally proposed by Kennedy and Eberhart in 1995 [3], is widely used to solve a variety of NP-complete problems like Scheduling [4] and task allocation [5], has become the new focus of research recently. Many PSO based algorithms have been proposed to minimize cost of executing workflow application on cloud computing [6].…”
Section: Introductionmentioning
confidence: 99%